Female pelvic medicine and reconstructive pelvic surgery / P. Drutz, S. Herschorn, and N.E. Diamant - Drutz, H.P.
During the last decade we have gained a better understanding of the function of the pelvic floor as a unit. The most common cause of insufficiency of the pelvic floor and its sphincters is the normal aging of its connective tissue, especially the collagen. It seems that this process can be counteracted by the influence of certain foreign bodies. Professor Chassar Moir of Oxford was one of the gynecologists who started using synthetic material in the slings at the Aldridge operation. He once told me that in some patients where he later had to make a laparotomy because of other diseases, he had found that the sling’s fixation at the aponeurosis had ruptured but the patient still was continent. To me it seemed very likely that it had been some type of action between the sling and the surrounding tissue which strengthened its structure. Instead of laying a muscle sling over the anterior parts of the divided muscle pubococcygeus at the levator plastic, I therefore tried to put a piece of nylon tissue over the sutured pubocervical ligaments. The result was that the nylon was expelled in single threads, but the patient became continent. After that I placed a piece of Marlex mesh as big as an ordinary postage stamp over the sutured pubocervical ligaments after the continence had been controlled with the bladder filled with 200 ml saline. With this technique five cases with stress incontinence were operated and cured at 5-year follow up. Unfortunately, I could not operate more patients with this technique because I had retired. One patient I had the possibility to control after 25 years. She was still continent at the age of 93 years.